Profile and experiences during the incarceration of transgender women and travestis (TGW) in Brazil: a cross-sectional study - Andréa Fachel Leal; Cristine Coelho Cazeiro; Ana Carolina Einsfeld Mattos; Bruna Hentges; Luciana Barcellos Teixeira; Daniela Riva Knauth; Laio Magno; Inês Dourado; Maria Amélia de Sousa Mascena Vera (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective: The objective of the present study is to describe the sociodemographic and behavioral characteristics of a group of transgender women and travestis (TGW) with a history of incarceration and the institutional and social context of this experience in Brazil. Methods: The analyzed data were derived from the TransOdara Study, a cross-sectional study conducted in five Brazilian capitals from December 2019 to July 2021. Participants were recruited using the Respondent-Driven Sampling (RDS) technique, in which, after an initial formative and exploratory stage, the first participants were identified; in turn, these participants recruited up to six other transgender women and travestis for the research. The study's outcome was the experience of incarceration throughout life, captured through the question: "Have you ever been arrested in your life?" Results: A total of 1,245 TGW were interviewed, of which 20.3% (n=253) experienced incarceration. Incarceration was more frequent among those aged 33 to 42 years (35.6%), with lower level of education (45.5%, p<0.001), engaged in informal work (30.3%), without a partner (67.2%), and among those who reported illicit drug use (66.4%). The majority (60.9%) of TGW were incarcerated with cisgender men, and the most common reasons for imprisonment were drug trafficking (30.4%) followed by robbery (29.2%). Over a quarter of the interviewees (26.3%) experienced assault, and 13.8% reported experiencing sexual violence during incarceration. Conclusion: The results emphasize the high prevalence of incarceration among TGW. This incarceration takes place in male wards and in a context of high rates of physical and sexual violence.